Human Herpesvirus 8 Seroprevalence among Prostate Cancer Case Patients and Control Subjects - Jenkins, F. J.; Hayes, R. B.; Jackson, A.; Pizza, G.; Mbisa, G.; Whitby, D.; Goedert, J. J. (The Journal of infectious diseases, 2007)
To investigate a possible association between human herpesvirus 8 (HHV-8) and prostate cancer, we evaluated HHV-8 seroprevalence in 2 case-control studies. HHV-8 antibodies were detected by immunofluorescence with cells expressing lytic viral proteins and by enzyme immunoassays with recombinant viral structural protein (K8.1) and latent protein (LANA-1; ORF73), respectively. HHV-8 seroprevalence tended to be lower in patients with prostate cancer than in control subjects, but there was no significant difference in either study. These data imply that HHV-8 is not a major prevalent cause of prostate cancer.